Mining Taxation : An Application to Mali - Thomas, Saji. (Washington, D.C. : International Monetary Fund, 2010)
Mali's gold sector is an enclave with weak forward and backward linkages with the rest of the economy. Given the predominance of the fiscal transmission channel, it is important that the design of the mineral tax regime gives the state a fair share of the benefits. Using optimal control theory, this paper estimates that the optimal royalty tax in Mali is about 3.5 percent. By reducing the royalty rate from 6 percent to 3 percent, Mali's mining code broadly ensures that the risk is shared between the state and mining companies, provides sufficient incentives to attract new exploration, and is comparable to the fiscal regimes in other sub-Saharan African countries in its mix of tax instruments and tax structure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet